Application of Educational Communication in Online Learning During the Covid-19 Pandemic on High School Student Achievement - Urrahmah, Syifa (Yana Research, 2023)
This study aims to determine the effect of implementing educational communication in online learning during the COVID-19 pandemic on student achievement at SMA Modal Bangsa Lhokseumawe. This study uses the theory of CMC (Computer Mediated Communication), with the limitation of research being limited to the online learning process which is only carried out during the COVID-19 pandemic. This type of research is quantitative research using statistical analysis. The variables in this study include the application of educational communication in online learning and the application of educational communication in online learning. The total population in this study was 341 students, the determination of the sample used total sampling. Data collection techniques using questionnaires indirectly (Online). The data analysis technique used is multiple coefficient analysis using the Product Moment correlation coefficient formula, and hypothesis testing using SPSS 25. The results show that the application of educational communication in online learning during the pandemic using CMC theory has an effect and significance on student achievement at SMA Modal Bangsa. This is evidenced by t arithmetic > t table (7.710 > 1.97).